Taking Care Triple P for Foster Parents With Young Children in Foster Care: Results of a 1-Year Randomized Trial - Job, Ann-Katrin (Journal of interpersonal violence, 2022)
Young children with a history of maltreatment or neglect in foster families often confront their caregivers with particularly challenging behaviors. This may lead to more parenting stress, an increased risk for the child in foster care to experience further maltreatment, and placement disruptions. We conducted a randomized controlled trial to investigate the efficacy of a parent group training tailored to the special needs of foster families. We hypothesized significant short- and long-term improvements regarding foster parents’ parenting competencies, child mental health problems, and related outcomes. Eighty-one families with 87 children in foster care aged 2 to 7 years participated in the trial. For the intervention study, 44 randomly selected families (54%) were offered to participate in the parent group training. Intervention and control group families were reassessed three times over a period of 1 year. Contrary to our expectations, we found no advantages of the intervention group compared with the usual care control group on any outcome measure. Instead, we found some significant changes in both groups across time. Placement into foster care is associated with some favorable outcomes for children in foster care. Additional support for foster families beyond the services delivered in the youth welfare system to foster parents was not associated with more favorable outcomes. The present intervention is likely associated with a low risk of harm but also with a high likelihood of a lack of significant benefits for foster parents and their young children going beyond feeling satisfied about the delivered services. Participating foster families showed favorable baseline results on parenting measures which may have impeded intervention effects to unfold on these proximal variables.